Canadian Stroke Best Practice Recommendations: Hyperacute Stroke Care Guidelines, Update 2015. Issue 6 (6th July 2015) - Casaubon, Leanne K.; Boulanger, Jean‐Martin; Blacquiere, Dylan; Boucher, Scott; Brown, Kyla; Goddard, Tom; Gordon, Jacqueline; Horton, Myles; Lalonde, Jeffrey; LaRivière, Christian; Lavoie, Pascale; Leslie, Paul; et al.
<x xml:space="preserve">Abstract</x> The 2015 update of the Canadian Stroke Best Practice Recommendations Hyperacute Stroke Care guideline highlights key elements involved in the initial assessment, stabilization, and treatment of patients with transient ischemic attack (TIA), ischemic stroke, intracerebral hemorrhage, subarachnoid hemorrhage, and acute venous sinus thrombosis. The most notable change in this 5th edition is the addition of new recommendations for the use of endovascular therapy for patients with acute ischemic stroke and proximal intracranial arterial occlusion. This includes an overview of the infrastructure and resources required for stroke centers that will provide endovascular therapy as well as regional structures needed to ensure that all patients with acute ischemic stroke that are eligible for endovascular therapy will be able to access this newly approved therapy; recommendations for hyperacute brain and enhanced vascular imaging using computed tomography angiography and computed tomography perfusion; patient selection criteria based on the five trials of endovascular therapy published in early 2015, and performance metric targets for important time‐points involved in endovascular therapy, including computed tomography‐to‐groin puncture and computed tomography‐to‐reperfusion times. Other updates in this guideline include recommendations for improved time efficiencies for all aspects of hyperacute stroke care with a movement toward a new median target door‐to‐needle time of 30 min, with the 90th percentile being 60 min. A stronger emphasis is placed on increasing public awareness of stroke with the recent launch of the Heart and Stroke Foundation of Canada FAST signs of stroke campaign; reinforcing the public need to seek immediate medical attention by calling 911; further engagement of paramedics in the prehospital phase with prehospital notification to the receiving emergency department, as well as the stroke team, including neuroradiology; updates to the triage and same‐day assessment of patients with transient ischemic attack; updates to blood pressure recommendations for the hyperacute phase of care for ischemic stroke, intracerebral hemorrhage, and subarachnoid hemorrhage. The goal of these recommendations and supporting materials is to improve efficiencies and minimize the absolute time lapse between stroke symptom onset and reperfusion therapy, which in turn leads to better outcomes and potentially shorter recovery times.